Cysteine boosters the evolutionary adaptation to CoCl2 mimicked hypoxia conditions, favouring carboplatin resistance in ovarian cancer - Nunes, Sofia C. (2018)
The authors would like to acknowledge the Instituto Português de Oncologia de Lisboa Francisco Gentil (IPOLFG) for partially funding the project. The study was also funded by Projecto TVI. This research was supported by Fundação para a Ciência e Tecnologia (FCT) (PhD ProRegeM program, PD/BD/105893/2014) and iNOVA4Health.